Selective Insertion of Nucleophiles to Terminal Epoxides through Ring Opening Sans Solvent - Sarma, Kuladip; Goswami, Amrit; R. Das, Manash (Current Organic Synthesis, 2015)
Application of silica nanopowder (15 nm) supported by potassium hydrogen sulphate has been demonstrated to be an effective recyclable catalyst system for the opening of terminal epoxide ring using alcohol and/or amine nucleophiles regioselectively at the terminal position in 3 hours at external temperature 70 °C. The terminal insertion of nucleophile has also been observed with potassium bisulphate supported on silica fume surface having particle size 100-150 nm with moderate products yield. Under this mild condition, no extra solvent is required
Keywords: epoxides